Gene profile in periodontal ligament cells and clones with enamel matrix proteins derivative - Idit Barkana (Blackwell Synergy, 2007)
Aim: Evaluate enamel matrix proteins derivative effect on gene expression profiles in cultured human periodontal ligament cell population and its clones. Material and Methods: Human periodontal ligament (PDL) cells were explanted. Cell cloning was performed and clones classified into fibroblastic (FB) and mineralized tissue forming (MTF) according to their capacity to express alkaline phosphatase and form mineralized tissue. All cell cultures were grown for 7 days, with and without enamel proteins added to the medium. Following RNA extraction, expression profiling was performed by hybridization with a DNA micro-array. Selected genes differed from the control at a significant level smaller than po0.01. Results: Enamel proteins induced major qualitative changes in mRNA expression in all PDL cell populations, differently affecting the entire PDL cell population and its clones. In the entire PDL cell population, enamel proteins significantly enhanced PDL cell function, with a general effect on enhanced cell functional metabolism. Conclusions: Enamel proteins enhanced gene expression responsible for protein and mineralized tissue synthesis in the entire PDL population. In the MTF clones, nucleic acid metabolism, protein metabolism and signal transduction related genes were upregulated, while in the FB clones, up-regulated genes were related to cell adhesion, nucleic acid metabolism and signal transduction.